2008
DOI: 10.1038/sj.bjc.6604818
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel and carboplatin vs gemcitabine and vinorelbine in patients with adeno- or undifferentiated carcinoma of unknown primary: a randomised prospective phase II trial

Abstract: Platinum/taxane combinations are widely used in patients with carcinoma of unknown primary (CUP), yielding response rates of 30% and median overall survival of 9 -11 months in selected patients. Yet these combinations have not been subject to a randomised trial to overcome selection bias, a major problem in CUP. We randomised 92 patients to either paclitaxel/carboplatin (arm A) or the non-platinum non-taxane regimen gemcitabine/vinorelbine (arm B). The primary endpoint was rate of practicability as defined: ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 22 publications
3
53
1
2
Order By: Relevance
“…40) and median OS of 6.5 months (95% CI 5.5-10.1) [65]. However, in comparison to nonplatinum based doublets such as gemcitabine-vinorelbine, carboplatin-paclitaxel remains superior in terms of both median OS (7.0 months vs 11.0 months) and 1-year survival rate (38% vs 29%) [66]. A comparative phase II study of carboplatin-docetaxel and cisplatindocetaxel revealed that both regimens had similar response (22% vs 26%) and median OS rates (8 months for each arm).…”
Section: Cancer Of Unknown Primary (Cup)mentioning
confidence: 99%
See 1 more Smart Citation
“…40) and median OS of 6.5 months (95% CI 5.5-10.1) [65]. However, in comparison to nonplatinum based doublets such as gemcitabine-vinorelbine, carboplatin-paclitaxel remains superior in terms of both median OS (7.0 months vs 11.0 months) and 1-year survival rate (38% vs 29%) [66]. A comparative phase II study of carboplatin-docetaxel and cisplatindocetaxel revealed that both regimens had similar response (22% vs 26%) and median OS rates (8 months for each arm).…”
Section: Cancer Of Unknown Primary (Cup)mentioning
confidence: 99%
“…The treatment of poorly differentiated CUP centres on carboplatin-based regimens including carboplatin-gemcitabine, carboplatin-paclitaxel and carboplatin-docetaxel [64][65][66]. The carboplatin-paclitaxel doublet appears to be effective in patients with predominantly nodal and pleural based metastasis of unknown origin with 68.4% ORR and median OS of 15 months [64].…”
Section: Cancer Of Unknown Primary (Cup)mentioning
confidence: 99%
“…69 In a randomized prospective phase II study conducted by the German CUP Study Group, the paclitaxel and carboplatin combination showed better clinical activity than the gemcitabine and vinorelbine combination. 70 The median overall survival, 1-year survival rate, and response rate were 11.0 months, 38%, and 23.8%, respectively, for patients treated with paclitaxel and carboplatin, compared with 7.0 months, 29%, and 20%, respectively, for those treated with gemcitabine and vinorelbine. Sequential treatment with paclitaxel/carboplatin/etoposide and gemcitabine/irinotecan was also found to be active in patients with occult primary tumors.…”
Section: Treatment Options Chemotherapymentioning
confidence: 99%
“…For example, metastases of adenocarcinoma in axillary lymph nodes in women will be treated as metastasized breast cancer, and metastases of squamous cell carcinoma in cervical lymph nodes will be treated as head and neck cancer [5,6]. For other CUPs that do not belong to a defined subcategory, standardized chemotherapeutic regimens have been proposed, too [3,7,8]. This is a pragmatic approach, since at one point, it is required to begin therapy and cease redundant search for the unknown primary, which will be diagnosed during the further course of disease in only 7% of patients [9].…”
Section: Introductionmentioning
confidence: 99%